Attempts to differentiate Xanthomonas campestris pv. phaseoli using inorganic salts. - Zapata, Mildred; Gaud, Rosario (Agronomía Mesoamericana, 2006)
Strains of Xanthomonas campestris pv. phaseoli (Xcp) isolated from common blight diseased bean leaves at Puerto Rico, Dominican Republic and Costa Rica were determined as pathogenic on the common bean, Phaseolus vulgaris. The strains determined by pathogenicity tests as pv. phaseoli were differentiated into pathovars such as phaseoli, vesicatoria, carotae, and xanthosoma by the use of the Biolog Identification System. Strains grown in 2, 3, 5-triphenyl tetrazolium chloride (TTC) showed a convex, shiny and smooth red pigment, a triphenyl formazan. No differences in virulence were found in the Xcp strains identified by pathogenicity tests. Two colony types were found in X. campestris. Also, colony types differences were found with Pseudomonas cissicola, P. fulva, Corynebacterium, Rhodococcus and Shingomonas.